Analysis of The Construction Management Application to Project Success Using Importance Performance Analysis on Superflat Concrete Floor Work - Pontan, Darmawan; Fikri, Imam Muhammad; Bhekti, Dhanu Setyo (Ridwan Institute, 2024)
In pursuit of Indonesia's equitable and sustainable development, the surge in industrial city development, notably in Karawang, has led to the construction of various facilities such as factories, warehouses, and workshops. Efficient planning methods, encompassing cost, time, and quality considerations, are imperative for these projects. A critical aspect is the construction of concrete floors, vital for supporting diverse loads like heavy vehicles, static loads from goods, storage racks, and large machines. The ongoing development of the Superflat Concrete Floor Method, with its productivity and precision advantages, underscores the need for effective construction management. This study aims to evaluate the substantial impact of construction management on project success and to map application indicators on the IPA diagram – Importance Performance Analysis. Employing both quantitative and qualitative methods, the research distributed questionnaires with Likert scales to 30 respondents, including contractors, owners, and design planners. Smartpls 3.0 software analysis reveals that Knowledge Management significantly and positively influences the success of the superflat concrete floor project at the Karawang Industrial Factory site. The IPA mapping places Knowledge Management and Total Quality Management in Quadrant I (Keep Up the Good Work), emphasizing their pivotal roles in ensuring project success. This study provides essential insights for stakeholders involved in industrial development, guiding them toward more effective construction management strategies for optimized outcomes.